Pengaruh Kemampuan Metakognitif Terhadap Indeks Prestasi Kumulatif Mahasiswa - Patrisius Afrisno Udil (Universitas Nusa Cendana, 2022)
Grade point average (GPA) is an indicator that describes the quality of student learning process. Students’ GPA is actually influenced by various factors, including metacognitive ability. This study aimed to determine the effect of metacognitive ability on the GPA of students of Mathematics Education Study Program, FKIP University of Nusa Cendana in the 2021/2022 academic year. The population in this study were all active students of the mathematics education study program for the 2021/2022 academic year. The research sample was students from the 2019/2020 class, consist of 89 students, that were chosen randomly. The instruments used were metacognitive ability questionnaire, while the documentation is carried out to obtain students’ GPA data from the academic section of the mathematics education study program. The data obtained were analyzed statistically with simple linear regression analysis techniques using SPSS 25. The results showed that there was significant effect of metacognitive ability on the GPA of mathematics education students at the University of Nusa Cendana. This is indicated by the value of Fcount = 13.439 > Ftable = 3.951 and the value of sig = 0.000 < . It also found that the magnitude of the influence given by metacognitive ability variable on students’ GPA is 13,4%, while the other 86,6% is influenced by other variables. The results of this study also show the regression equation model .